Reinforcing Factors Of Religious Tolerance In Parenting Within Gunungkidul’s Religious Moderation Village: An Interpretative Phenomenological Analysis - Angga Anandika Putra; Siti Rohmah Nurhayati (Eduvest - Journal of Universal Studies, 2026)
Religious tolerance education within the family has become increasingly important amid the growing challenges of the digital era, in which children are exposed to diverse information, including intolerant and radical narratives. Although previous studies have explored factors influencing religious tolerance, limited attention has been given to how parents strengthen tolerance values through parenting practices, particularly in religiously plural communities. This study aimed to identify the reinforcing factors that enabled parents in Gunungkidul’s Religious Moderation Village to consistently instill and practice religious tolerance values in parenting. This research employed a qualitative approach with an interpretative phenomenological design. Data were collected through in-depth interviews with six fathers from interfaith communities in Watusigar and Hargomulyo Villages, Gunungkidul Regency, who were selected using purposive sampling. Data were analyzed using Interpretative Phenomenological Analysis (IPA) to identify meaningful experiences and emerging themes. The findings revealed two major reinforcing factors: the pluralistic social environment as a natural learning space and the support of state legality and national philosophical values, including Pancasila and Bhinneka Tunggal Ika. These factors reduced parents’ educational burdens by transforming tolerance from a conceptual lesson into an everyday lifestyle experienced by children. The study concludes that sustainable religious tolerance in parenting is strengthened through the synergy between supportive social ecosystems and formal state structures, providing important implications for inclusive family education and religious moderation practices.